Легенды о русских героях - Мартиросова Мария Альбертовна (История России, 2010)
Экземпляры: Ч/з Дб, ф. 3 (20111026) / Инвентарный номер: 97522 / Цена: 173.52 / Сис.шифр: 63.3(2) / Авт.знак: М 29 / ББК: 63.3(2)